PROFESSIONAL AND PEDAGOGICAL COMMUNICATION OF TEACHERS OF HIGHER EDUCATION INSTITUTIONS: CHALLENGES OF WAR - Nataliia P. Volkova; Olha V. Lebid (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2022)
The article investigates the problem of professional and pedagogical communication of teachers of higher education institutions during the war. The purpose of the article is to reveal the phenomenon of «professional and pedagogical communication», the presentation of new accents of professional and pedagogical communication, which must be considered by the teacher in higher education in wartime. Professional and pedagogical communication is understood as a system of direct or indirect connections and interactions of the teacher, which are realized through both verbal and nonverbal means, as well as computer communication tools for information exchange, modeling and management of communication, regulation of professional pedagogical relations. It is noted that the established concept of professional and pedagogical communication in the war has gained renewed importance and needs new accents, namely: shifted attention to the subjects of communication, which are carriers of the active, transformative principle, which is a communicatively educated person, able to consciously plan and organize their own communicative activities, influence the partner, in some way perceive, analyze the informational, emotional and intellectual content of speech, psychophysiological and energy states and evaluate them; has a developed emotional intelligence, communication skills, abilities, experience. Emphasis is placed on establishing effective interaction of participants in the educational process through the organization of personality-oriented, emotional and supportive communication, based on impartiality, sincere interest, support, care for each other; shifting the emphasis in the educational process from teaching to learning, organizing the teaching process not as a transition of information, but as facilitation of the processes of meaningful and conscious learning. The essence of the concepts «personality-oriented communication of the teacher», «emotional-supportive communication of the teacher» is revealed; the principles of emotional and supportive communication of a teacher of a higher education institution are determined; the importance of reflexive (active) listening during the professional and pedagogical communication of the teacher in the conditions of war is substantiated; effective methods of reflexive listening (clarification, paraphrasing, reflection of feelings, summarizing) are revealed; the characteristics of pedagogical facilitation are distinguished (cooperation, own position, individuality and equality, self-disclosure, involvement of everyone in joint activities, organization of space). It is concluded that only a teacher who trusts students, recognizes their uniqueness, is interested in their life, problems, is always ready to help, can show students openness and accessibility, create for them the opportunities to express thoughts and feelings, a sense of involvement in the educational process, protection from environmental threats.